Association between severity of periodontitis and rheumatoid arthritis - Izzati Chatyarianti CHANAL; Agus SUSANTO; Ira KOMARA (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT Many studies have shown a correlation between periodontitis and rheumatoid arthritis, and both areinflammatory diseases that cause damage to their surrounding tissues and have similar characteristics. Periodontitiscan cause an increased erythrocyte sedimentation rate and C-reactive protein in rheumatoid arthritis (RA) patientsand can cause systemic inflammation in RA. This review aims to assess the association between the severity ofperiodontitis and rheumatoid arthritis. The method of this study is scoping review. PRISMA method is used as aguideline for searching and selecting articles using four electronic databases with criteria (P: Population)periodontitis and rheumatoid arthritis patients, (C: Concept) Relationship between periodontitis and rheumatoidarthritis, (C: Context) periodontal medicine. Articles selection based on the inclusion criteria: journals published in2011-2020, research methods using case-control, cohort, or RCT, subjects diagnosed with RA and Periodontitis, andsubjects age at least 18 years old and exclusion criteria are subjects were pregnant and issues diagnosed with otherdiseases. Six articles included one cohort study and five case-control studies. The result showed a positivecorrelation between periodontitis and RA. There is an association between the severity of periodontitis andrheumatoid arthritisKEYWORDS: Periodontitis, periodontal disease, rheumatoid arthritis